hello everyone, I am currently working on an assignment and have solved my problem down to the following:
I have graphed both functions and seen that a solution exists that is not 0 and I am lost as to how to find the exact solution.
If anyone can help that would be greatly appreciated.
This isn't what skeeter (or I) would call an "elementary algebraic method" but:
Multiply both sides by : or . Now let y= x- 3 so that x= y- 3 and the equation becomes so .
Now use "Lambert's W function" which is defined as the inverse to the function f(x)= . In this case so that . That is, as I said, not an "elementary algebraic" method but it is as good a solution as "x= cos(3)" or "x= log(5)" would be.